Root rots - Abawi, G.S. (International Center for Tropical Agriculture, 1989)
Beans are attacked by different pathogens. Rhizoctonia root rot results in seed rot, damping-off, stem canker, and root and pod rot. Fungicide applications are suggested as control measures. Fusarium root rot appears as reddish lesions or streaks on the hypocotyl and primary root. Fusarium yellows occurs on the roots and hypocotyls, usually at wound sites. Initial symptoms appear on lower leaves, which exhibit yellowing and wilting, becoming stronger and progressing upward to younger leaves. Control measures include crop rotation and chemical seed treatment. Pythium root rot is caused by various species of Pythium (P. ultimum, P. irregulare, P. aphanidermatum, and P. myriotylum). It can infect germinating seed, cotyledons, terminal buds, radicle, and hypocotyl tissue. Southern blight produces damping-off, stem blight, and root rot. Control can be achieved by selecting fields with low soil acidity and good drainage, wide plant spacing, lime, and crop rotation. Black root rot infects the hypocotyl. Numerous elongated lesions are produced on the stem and root tissues, resulting in plant stunting, premature defoliation, and eventual plant death. Texas root rot or Phymatotrichum root rot infects under-ground plant parts. Aboveground symptoms are stunting and sudden wilting at blossom initiation. Plants with Aphanomyces root-and-hypocotyl rot are stunted, clorotic, and suffer premature defoliation. Control measures for most of these diseases include proper cultural practices, use of chemicals, and resistant var. Color illustrations are given of the symptoms and damage caused by the diseases. (CIAT)